Green synthesized Se–ZnO/attapulgite nanocomposites using Aloe vera leaf extract: Characterization, antibacterial and antioxidant activities. (1st August 2022) - Song, Yameng; Yang, Fangfang; Ma, Mengting; Kang, Yuru; Hui, Aiping; Quan, Zhengjun; Wang, Aiqin
Abstract: In this work, a green phyto-mediated method was developed to synthesize attapulgite (APT) supported Se–ZnO nanoparticles (NPs) nanocomposites (Se–ZnO/APT) using Aloe vera leaf extract (ALE) as a reductant and stabilizer. Transmission electron microscopy (TEM) images showed that the monodispersed Se1 –ZnO1 NPs with the average size of 50.07 nm decorated on the APT surface while pure Se1 –ZnO1 NPs agglomerated, indicating that APT played an important role in the anchor and dispersion of NPs. Fourier transform infrared spectroscopy (FT-IR) results revealed that the alcohols, phenols and proteins from ALE may play pivotal roles in reducing and capping Se–ZnO NPs. FT-IR and X-ray photoelectron spectroscopy (XPS) analyses confirmed the hydrogen bonding interactions between Se–ZnO NPs and APT. Antibacterial results demonstrated that Se–ZnO/APT nanocomposites had good antibacterial activities against Staphylococcus aureus, Escherichia coli, methicillin-resistant Staphylococcus aureus and extended-spectrum β -lactamase-producing Escherichia coli that were comparable to that of Se–ZnO NPs, indicating that the introduction of APT exerted a synergistic effect. Antioxidant results showed that Se–ZnO/APT also exhibited good scavenging capacity for hydroxyl radicals. Additionally, the bioactivities were strengthened with increasing Se content in Se–ZnO NPs. This study provided a new strategy to construct a good-property nanocomposite that will have great potential in the food preservation field. Graphical abstract: Image 1 Highlights: Se–ZnO/APT nanocomposites were biosynthesized using Aloe vera leaf extract. APT as a support could reduce the agglomeration of Se–ZnO NPs. More content of Se doped in ZnO could enhance bioactivities. Se–ZnO/APT exhibited good antibacterial and antioxidant activities. Synergistic effect was produced by Se-doping and APT-supporting.